TRANSPARANSI WEDDING ORGANIZER DENGAN SISTEM MONITORING BERBASIS WEB MENGGUNAKAN REACT BERBASIS BOOTSTRAP - Yasir Abduzzhohir; Farid Nugraha Wijaya; Assidiq Nurrochman; Muhammad Akhyar; Didik Haryadi; Yana Adharani; Rully Mujiastuti (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Wedding organizers are professional service providers in planning and managing wedding events that require transparent and well-structured information management. This study aims to improve participants’ understanding of applying modern web technologies in developing a transparent and efficient wedding organizer monitoring system. The method used was a descriptive approach implemented through webinar and workshop activities, including socialization, material delivery, hands-on practice, and evaluation using pre-test and post-test instruments. The results indicate an improvement in participants’ understanding, as reflected by post-test results in which most questions achieved correct answer percentages above 70% compared to the pre-test. Furthermore, participant feedback showed a high level of satisfaction, with 56.6% of participants strongly agreeing and 40.7% agreeing with the quality of the materials and the implementation of the activities. These findings indicate that the activities were effective in enhancing participants’ knowledge and practical skills.